Why do we pay? A national survey of investigators and IRB chairpersons - Ripley, Elizabeth (2010)
The principle that payment to participants should not be undue or coercive is the consensus of international and national guidelines and ethical debates; however, what this means in practice is unclear. This study determined the attitudes and practices of IRB chairpersons and investigators regarding participant payment. One thousand six hundred investigators and 1900 IRB chairpersons received an invitation to participate in a web-based survey. Four hundred and fifty-five investigators (28.3%) and 395 IRB chairpersons (18.6%) responded. The survey was designed to gather considerations that govern payment determination and practical application of these considerations in hypothetical case studies. The survey asked best answer, multiple choice, and open text questions. Short hypothetical case scenarios where presented, and participants were asked to rate factors in the study that might impact payment and then determine their recommended payment. A predictive model was developed for each case to determine factors which affected payment. Although compensation was the primary reason given to justify payment by both investigators and IRB chairpersons, the cases suggested that, in practice, payment is often guided by incentive, as shown by the impact of anticipated difficulty recruiting, inconvenience, and risk in determining payment. Payment models varied by type of study. Ranges for recommended payments by both groups for different types of procedures and studies are presented.